Diversity and variability of secondary metabolites in gynura procumbens: a systematic review - Othman, Nur Ain Najihah (2017)
Gynura procumbens from Asteraceae family are widely used as medicinal plant in Southeast Asia. Publications in English, Malay and Indonesian languages, abstract and full-text articles, in vitro and vivo studies and conference proceeding on secondary metabolites of G. procumbens are included in this study. A total of 43 articles were screened for their medicinal values and secondary metabolites. The result shows that G. procumbens exerts an anti hyperglycemic, anti-ulcer, anti-inflammatory, anti-cancer, anti-hypertensive, anti-oxidant, hepatoprotective effect, immunomodulator, reproductive system enhancer amd anti-angiogenic effect. Thus, this review on medicinal values and secondary metabolites of G. procumbens would provide extensive information about this plant and could be used as a reference for future researcher that has similar interest on this plant.